Different survival outcomes after curative R0-resection for Eastern Asian and European gastric cancer: Results from a propensity score matched analysis comparing a Korean and a German specialized center. Issue 28 (July 2016) - Kim, Young-Woo; Joo, Jungnam; Yoon, Hong Man; Eom, Bang Wool; Ryu, Keun Won; Choi, Il Ju; Kook, Myeong Cherl; Schuhmacher, Christoph; Siewert, Joerg Ruediger; Reim, Daniel
Abstract : Abstract: Several retrospective analyses on patients who underwent gastric cancer (GC) surgery revealed different survival outcomes between Eastern (Korean, Japanese) and Western (USA, Europe) countries due to potential ethnical and biological differences. This study investigates treatment outcomes between specialized institution for GC in Korea and Germany. The prospectively documented databases of the Gastric Cancer Center of the National Cancer Center, Korea (NCCK) and the Department of Surgery of the Technische Universitaet Muenchen (TUM), Germany were screened for patients who underwent primary surgical resection for GC between 2002 and 2008. Baseline characteristics were compared using χ 2 testing, and 2 cohorts were matched using a propensity score matching (PSM) method. Patients' survival was estimated using Kaplan–Meier method, and multivariable Cox proportional hazard model was used for comparison. Three thousand seven hundred ninety-five patients were included in the final analysis, 3542 from Korea and 253 from Germany. Baseline characteristics revealed statistically significant differences for age, tumor location, pT stage, grading, lymphatic vessel infiltration (LVI), comorbidities, number of dissected lymph nodes (LN), postoperative complications, lymph-node ratio stage, and application of adjuvant chemotherapy. After PSM, 171 patients in TUM were matched to NCCK patients, and baseline characteristics for both cohorts were well balanced. Patients in Korea had significantly longer survival than those in Germany both before and after PSM. When the analysis was performed for each UICC stage separately, same trend was found over all UICC stages before PSM. However, significant difference in survival was observed only for UICC I after PSM. This analysis demonstrates different survival outcomes after surgical treatment of GC on different continents in specialized centers after balancing of baseline characteristics by PSM.